Bacteria as a treasure house of secondary metabolites with anticancer potential. (November 2022) - Mohan, Chakrabhavi Dhananjaya; Rangappa, Shobith; Nayak, S. Chandra; Jadimurthy, Ragi; Wang, Lingzhi; Sethi, Gautam; Garg, Manoj; Rangappa, Kanchugarakoppal S.
Abstract: Cancer stands in the frontline among leading killers worldwide and the annual mortality rate is expected to reach 16.4 million by 2040. Humans suffer from about 200 different types of cancers and many of them have a small number of approved therapeutic agents. Moreover, several types of major cancers are diagnosed at advanced stages as a result of which the existing therapies have limited efficacy against them and contribute to a dismal prognosis. Therefore, it is essential to develop novel potent anticancer agents to counteract cancer-driven lethality. Natural sources such as bacteria, plants, fungi, and marine microorganisms have been serving as an inexhaustible source of anticancer agents. Notably, over 13, 000 natural compounds endowed with different pharmacological properties have been isolated from different bacterial sources. In the present article, we have discussed about the importance of natural products, with special emphasis on bacterial metabolites for cancer therapy. Subsequently, we have comprehensively discussed the various sources, mechanisms of action, toxicity issues, and off-target effects of clinically used anticancer drugs (such as actinomycin D, bleomycin, carfilzomib, doxorubicin, ixabepilone, mitomycin C, pentostatin, rapalogs, and romidepsin) that have been derived from different bacteria. Furthermore, we have also discussed some of the major secondary metabolites (antimycins, chartreusin, elsamicins, geldanamycin, monensin, plicamycin, prodigiosin, rebeccamycin, salinomycin, and salinosporamide) that are currently in the clinical trials or which have demonstrated potent anticancer activity in preclinical models. Besides, we have elaborated on the application of metagenomics in drug discovery and briefly described about anticancer agents (bryostatin 1 and ET-743) identified through the metagenomics approach.